2023
DOI: 10.3390/pharmaceutics15041126
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ε-Caprolactone Implants for Benznidazole Prolonged Release: An Alternative to Chagas Disease Oral Treatment

Abstract: Benznidazole (BZ) tablets are the currently prescribed treatment for Chagas disease. However, BZ presents limited efficacy and a prolonged treatment regimen with dose-dependent side effects. The design and development of new BZ subcutaneous (SC) implants based on the biodegradable poly-ɛ-caprolactone (PCL) is proposed in this study for a controlled release of BZ and to improve patient compliance. The BZ–PCL implants were characterized by X-ray diffraction, differential scanning calorimetry, and scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The lower treatment activity observed with the 24-treatment formulations compared to BZ may be attributed to the possibility of the slow release of drugs from formulations containing PEG and PCL polymeric carriers [ 52 , 84 ]. It is possible that BZ was released in concentrations insufficient to promote a reduction like that observed in treatments with free BZ at the concentrations mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower treatment activity observed with the 24-treatment formulations compared to BZ may be attributed to the possibility of the slow release of drugs from formulations containing PEG and PCL polymeric carriers [ 52 , 84 ]. It is possible that BZ was released in concentrations insufficient to promote a reduction like that observed in treatments with free BZ at the concentrations mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, polymeric carriers offer several advantages, including the potential to reduce adverse effects, increase drug stability, and improve the solubility and effects of the drug [ 86 , 87 ]. In this context, studies evaluating BZ dissolution in new formulations and in in vivo activity have demonstrated an increase in both dissolution and activity [ 84 , 88 , 89 , 90 ]. These findings suggest that the formulations presented in this work hold promise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations